Deferred Aspirations and Structural Poverty: Psychological-Spiritual Barriers and Community-Based Empowerment in Islamic Education Among Rural Youth in Indonesia - Arinal Inayah; Syamsudin Aziz Saputra; Nasirudin Nasirudin (Yayasan Pendidikan Haiba Nasywa, 2026)
This research seeks to investigate the phenomenon of “deferred aspirations” caused by financial limitations that obstruct the accessibility and development of Islamic education among youth in Sugiharjo Village, Tuban Regency, East Java, Indonesia, through a qualitative case study approach involving 8 informants at the research site in Sugiharjo, Tuban, Indonesia consisting of adolescents, parents, teachers, religious leaders, and community representatives. Data were collected through informal interviews, participatory observation, and document analysis, then analyzed using the Miles and Huberman framework. The findings reveal that poverty is not merely an economic barrier but also a structural mechanism that triggers a multidimensional educational decline, reflected in phenomena such as “forced school exits,” “hidden participation exclusion,” and “quality compromises,” where students remain formally enrolled yet experience limited access to meaningful educational opportunities. In addition, the study identifies serious psychological consequences, including “educational fatalism,” “dual cognitive load,” and “institutional shame,” which weaken adolescents’ confidence, motivation, and emotional attachment to educational institutions. Despite these challenges, the research highlights several transformative community-based solutions rooted in local religious and social solidarity, including the revitalization of “community-run Education Zakat,” the implementation of a “School While Working” model in collaboration with micro, small, and medium enterprises (MSMEs), and the formation of “Gotong Royong Study Groups” that encourage collective learning and mutual assistance. These findings emphasize the importance of shifting educational intervention frameworks from passive charitable approaches toward participatory empowerment strategies that maximize local social and spiritual capital to break the cycle of structural poverty. Ultimately, this study contributes a new conceptual framework integrating psychological-spiritual dimensions with grassroots economic empowerment as a foundation for more inclusive Islamic education policies in marginalized rural communities.